Gene Expression in Skin, Muscle, and Dorsal Root Ganglion after Plantar Incision in the Rat - Spofford, Christina M. (2012)
BACKGROUND: Treating postoperative pain remains a significant challenge for perioperative medicine. Recent studies have shown that nerve growth factor is upregulated and contributes to incisional pain. To date, few studies have examined expression of other neurotrophin-related mediators that may contribute to the development and/or maintenance of incisional pain. METHODS: Male, Sprague-Dawley rats underwent a plantar incision and pain behaviors were examined (n = 6). In a separate group of rats, expression of neurotrophic factors were studied. At various times after incision (n = 4) or sham surgery (n = 4), the skin, muscle and dorsal root ganglia were harvested and total RNA isolated. Real-time reverse transcription polymerase chain reaction was performed and the fold change in gene expression was analyzed using significance analysis of microarrays. RESULTS: Several genes were changed (p < 0.05) as early as one hour after incision. Expression of artemin and nerve growth factor were increased in both incised skin and muscle. Brain-derived neurotrophic factor, neurotrophin-3, and neurotrophin-5 were all downregulated in the skin but upregulated in the muscle 48 h after incision. Few genes changed in the dorsal root ganglion. Most changes in expression occurred in the first 48 h after incision, a timeframe when pain behavior was the greatest. CONCLUSION: Surgical incision is associated with pain-related gene expression changes in skin, muscle, and to a lesser extent, dorsal root ganglion. The gene expression profile provides clues as to mediators that are involved in peripheral sensitization and pain transmission after surgical incision and also suggest mechanisms for resolution of postoperative pain when more persistent pain syndromes like neuropathic pain continue.